Heteroleptic arene Ru(ii) dipyrrinato complexes: DNA, protein binding and anti-cancer activity against the ACHN cancer cell line. Issue 16 (24th March 2016) - Gupta, Rakesh Kumar; Kumar, Amit; Paitandi, Rajendra Prasad; Singh, Roop Shikha; Mukhopadhyay, Sujay; Verma, Shiv Prakash; Das, Parimal; Pandey, Daya Shankar
Abstract : The in vitro cytotoxicities of heteroleptic Ru(ii ) complexes were studied in ACHN cell lines by MTT assay, DNA cleavage, (AO/EtBr) and FACS analysis. Abstract : Four organometallic complexes [(η 6 -C6 H6 )RuCl(pmpzdpm)], 1 ; [(η 6 -C6 H6 )RuCl(pypzdpm)], 2 ; [(η 6 -C10 H14 )RuCl(pmpzdpm)], 3 and [(η 6 -C10 H14 )RuCl(pypzdpm)], 4 containing 5-(2-pyrimidyl-piperazine)phenyldipyrromethene (pmpzdpm) and 5-(2-pyridylpiperazine)phenyldipyrromethene (pypzdpm) have been designed and synthesized. The complexes1–4 have been fully characterized by elemental analyses and spectroscopic studies (ESI-MS, IR, 1 H, 13 C NMR, UV–vis). Their electrostatic/intercalative interaction with CT DNA has been investigated by UV–vis and competitive ethidium bromide displacement studies while their protein binding affinity toward bovine serum albumin (BSA) was realized by UV–vis, fluorescence, synchronous and three dimensional (3D) fluorescence studies. The interaction with DNA and protein has further been validated by in silico studies. Cellular uptake, in vitro cytotoxicity and flow cytometric analyses have been performed to determine the mode of cell death against the kidney cancer cell line ACHN. Cell cycle analysis suggested that the complexes cause cell cycle arrest in the subG1 phase and overall results indicated that the in vitro antitumor activity of1–4 lies in the order of3 >4 >1 >2 (IC50, 7.01 ; 8.02 ; 2.03 ; 4.0 μM, 4 ).